2019
DOI: 10.1080/21645515.2019.1682845
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in healthcare providers’ interpretations and implementations of ACIP’s meningococcal vaccine recommendations

Abstract: Invasive meningococcal disease (IMD) caused by the bacteria Neisseria meningitidis is rare but potentially fatal. For healthy adolescents, the US Advisory Committee on Immunization Practices (ACIP) recommends routine vaccination with MenACWY and recommends MenB vaccination under shared clinical decision-making (previously "Category B"). The recommendation for MenB vaccination was the first category B recommendation in adolescents, and it is unclear how healthcare providers (HCPs) implement these guidelines. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…For example, one study in the United Kingdom reported that while most parents recognized meningitis as a life-threatening disease, many were not aware of the MenB vaccine [168]. In the United States, studies have indicated that healthcare providers are not frequent prescribers of MenB vaccines, potentially because of a general lack of knowledge of serogroup B disease and the available vaccines as well as an inability to define official vaccination guidelines [30,31]. In Greece, where MenB vaccination is not included in the national immunization plan, pediatricians may hesitate to recommend vaccination to parents owing to high out-of-pocket costs [169].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study in the United Kingdom reported that while most parents recognized meningitis as a life-threatening disease, many were not aware of the MenB vaccine [168]. In the United States, studies have indicated that healthcare providers are not frequent prescribers of MenB vaccines, potentially because of a general lack of knowledge of serogroup B disease and the available vaccines as well as an inability to define official vaccination guidelines [30,31]. In Greece, where MenB vaccination is not included in the national immunization plan, pediatricians may hesitate to recommend vaccination to parents owing to high out-of-pocket costs [169].…”
Section: Discussionmentioning
confidence: 99%
“…Because MenACWY vaccines do not provide protection against serogroup B, this suggests that some patients may not be sufficiently protected against the spectrum of disease-causing meningococcal strains. This possible misconception, as well as confusion over official vaccination guidelines [30,31], may be tied to the infrequent prescribing of MenB vaccines by US healthcare professionals, with only 22% of 17-year-olds in this region receiving ≥1 dose of the multidose series in 2019 [32]. Therefore, further guidance for healthcare professionals is vital to support a recommendation of MenB vaccine to their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work also suggests a link between socioeconomic inequities and provider prescribing behavior. In a nationally representative survey, HCPs who prescribed MenB vaccines (compared with those who prescribed MenACWY only) were most likely to be seeing patients with private or commercial healthcare plans (i.e., not Medicaid) [ 40 ]. Additional findings from the aforementioned study from the Philadelphia region of 45,428 patients (aged 16–23 years) revealed lower MenB vaccine uptake among those seen in urban practice locations (vs suburban practice locations) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with these results, previous research has indicated that parents expect providers to guide them on adolescent vaccines and cite the provider's office as the most common information source for knowing when their adolescents' vaccines are due [24]. The ACIP recommended that MenB vaccination be available to adolescents and young adults through provider-patient discussion and shared clinical decision-making (i.e., a Category B recommendation) [21], yet studies have shown that providers have a poor understanding of MenB vaccines and this ACIP recommendation [29,36,[38][39][40]; Category B designation has paradoxically been shown to be the factor that hinders MenB vaccination [29,38,39]. In a nationally representative sample of US providers surveyed in 2016 by Kempe and colleagues, only 38% of family physicians and 56% of pediatricians were able to correctly define a Category B recommendation [29].…”
Section: Healthcare Provider Impact On Menb Vaccine Awareness and Uptakementioning
confidence: 99%
“…HPV vaccine recommendations vary based on the age at initiation, and other vaccines are only recommended for specific risk groups (e.g., pneumococcal polysaccharide vaccine for individuals under 64 with chronic medical or immunocompromising conditions) [ 1 ]. Recently, the Advisory Committee on Immunization Practices (ACIP) has also recommended shared clinical decision-making for several vaccines, including the HPV vaccine for adults over the age of 26 [ 4 ], pneumococcal conjugate vaccine for adults over the age of 65 without other indications for the vaccine [ 5 ], and the meningococcal serogroup B vaccine [ 6 ]. However, what “shared clinical decision-making” means remains unclear to many physicians [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%